Gerenciamento de projetos de extensão universitária: um estudo de caso do Núcleo Ouroboros de Divulgação Científica - Patracão, Sandra Mierro (Universidade Federal de São Carlos, 2022)
The university extension has an essential role in articulating the university and society. Through extension, academics put into practice what they have learned in the classroom, while people in society benefit from this learning. Extension actions take place through programs, projects, and university extension activities. In this context, the present work proposed to observe the practice of the projects of the University Extension Program “Núcleo Ouroboros de Divulgação Científica” of the Federal Univsrsity of São Carlos, Campus São Carlos, linked to the Departament of Chemistry, with the objective of identifying possible difficulties that envolve its execution. Research with a qualitative, exploratory, descriptive approach, where the case study strategy was used. Data was collected through documental research, participant observation, and semi-structured interviews with coordinators and the Ouroboros work team. The results of the analysis showed lapses in the procedures for processing projects whitin the scope of UFSCar, proved the academic and social relevance of university extension and indicated the lack of physical, financial, and human resources as the main difficulties for carrying out the extension projects of the Núcleo Ouroboros de Divulgação Científica, in particular.
Management of university extension projects: a case study of the Ouroboros Center for Scientific Dissemination
Keywords: Extensão Universitária; Projeto de Extensão; Ouroboros; UFSCar; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO